Cancer Incidence in First- and Second-Degree Relatives of BRCA1 and BRCA2 Mutation Carriers. (15th June 2016) - Streff, Haley; Profato, Jessica; Ye, Yuanqing; Nebgen, Denise; Peterson, Susan K.; Singletary, Claire; Arun, Banu K.; Litton, Jennifer K.
Abstract : Background: Mutations in the BRCA1 and BRCA2 genes are associated with increased risk of breast, ovarian, and several other cancers. The purpose of the present study was to evaluate the incidence of cancer in first- and second-degree relatives of BRCA mutation carriers compared with the general population. Materials and Methods: A total of 1, 086 pedigrees of BRCA mutation carriers was obtained from a prospectively maintained, internal review board-approved study of persons referred for clinical genetic counseling at the University of Texas MD Anderson Cancer Center. We identified 9, 032 first- and second-degree relatives from 784 pedigrees that had demonstrated a clear indication of parental origin of mutation. Standardized incidence ratios (SIRs) were used to compare the observed incidence of 20 primary cancer sites to the expected incidence of each cancer based on the calculated risk estimates according to each subject's age, sex, and ethnicity. Results: BRCA1 families had increased SIRs for breast and ovarian cancer ( p < .001) and decreased SIRs for kidney, lung, prostate, and thyroid cancer and non-Hodgkin's lymphoma ( p < .001). BRCA2 families had increased SIRs for breast, ovarian, and pancreatic cancer ( p < .001) and decreased SIRs for kidney, lung, thyroid, and uterine cancer and non-Hodgkin's lymphoma ( p < .0025). Analysis of only first-degree relatives ( n = 4, 099) identified no decreased SIRs and agreed with the increased SIRs observed in the overall study population. Conclusion: We have confirmed previous reports of an association between breast, ovarian, and pancreatic cancers with BRCA mutations. Additional research to quantify the relative risks of these cancers for BRCA mutation carriers can help tailor recommendations for risk reduction and enhance genetic counseling. Abstract : Previous reports of an association between breast, ovarian, and pancreatic cancers with BRCA mutations have been confirmed. Additional research to quantify the relative risks of these cancers for BRCA mutation carriers can help tailor recommendations for risk reduction and enhance genetic counseling.